G2/M checkpoint regulation and apoptosis facilitate the nuclear egress of parvoviral capsids - Mattola, Salla; Mäntylä, Elina; Aho, Vesa; Salminen, Sami; Leclerc, Simon; Oittinen, Mikko; Salokas, Kari; Järvensivu, Jani; Hakanen, Satu; Ihalainen, Teemu O; Viiri, Keijo; Vihinen-Ranta, Maija (Frontiers in Cell and Developmental Biology, 2022)
The nuclear export factor CRM1-mediated pathway is known to be important for the nuclear egress of progeny parvovirus capsids in the host cells with virus-mediated cell cycle arrest at G2/M. However, it is still unclear whether this is the only pathway by which capsids exit the nucleus. Our studies show that the nuclear egress of DNA-containing full canine parvovirus. capsids was reduced but not fully inhibited when CRM1-mediated nuclear export was prevented by leptomycin B. This suggests that canine parvovirus capsids might use additional routes for nuclear escape. This hypothesis was further supported by our findings that nuclear envelope (NE) permeability was increased at the late stages of infection. Inhibitors of cell cycle regulatory protein cyclin-dependent kinase 1 (Cdk1) and pro-apoptotic caspase 3 prevented the NE leakage. The change in NE permeability could be explained by the regulation of the G2/M checkpoint which is accompanied by early mitotic and apoptotic events. The model of G2/M checkpoint activation was supported by infection-induced nuclear accumulation of cyclin B1 and Cdk1. Both NE permeability and nuclear egress of capsids were reduced by the inhibition of Cdk1. Additional proof of checkpoint function regulation and promotion of apoptotic events was the nucleocytoplasmic redistribution of nuclear transport factors, importins, and Ran, in late infection. Consistent with our findings, post-translational histone acetylation that promotes the regulation of several genes related to cell cycle transition and arrest was detected. In conclusion, the model we propose implies that parvoviral capsid egress partially depends on infection-induced G2/M checkpoint regulation involving early mitotic and apoptotic events.